2020
DOI: 10.1002/acm2.12845
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and safety increases after the implementation of a multi‐institutional automated plan check tool at our institution

Abstract: Purpose: The plan check tool (PCT) is the result of a multi-institutional collaboration to jointly develop a flexible automated plan checking framework designed with the versatility to be shared across collaborating facilities while supporting the individual differences between practices. We analyze the effect that PCT has had on the efficiency and effectiveness of initial chart checks at our institution.Methods and Materials: Data on errors identified during initial chart checks were acquired during two time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…We expect that clinical use of our chart review solution will provide data on the frequency of different types of errors encountered as has been reported in other studies 12,13,24,23 . This will permit subsequent data mining for a more complete risk assessment, and concomitant risk reduction 25 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We expect that clinical use of our chart review solution will provide data on the frequency of different types of errors encountered as has been reported in other studies 12,13,24,23 . This will permit subsequent data mining for a more complete risk assessment, and concomitant risk reduction 25 .…”
Section: Discussionmentioning
confidence: 85%
“…A key recommendation of AAPM Task Group 275, the objective of which was to provide recommendations on the physics chart review, is the development of automated tools to assist with the chart review task 1 . Most current automated and semi‐automated chart review tools are similar to an automated checklist to verify the integrity of variables in a specific module or their consistency across software components used to create the treatment plan based on predefined rules 5–14 . Several studies have shown the use of such tools to increase efficiency and patient safety and to reduce the rate of plan revisions, avoidable safety events, and patient delays 10,11,13 …”
Section: Introductionmentioning
confidence: 99%
“…Even with the integrated planning system and RO‐EMR system, some communication errors listed in Table 4 still require manual checks such as the use of bolus and instruction of isocenter shifts. A recent publication from MSKCC, under the integrated environment of the treatment planning and RO‐EMT systems, indicated that their automatic plan check tool reported three outputs for their checked items: pass, flag, and report 15 . The items labeled with “flag” or “report” require manual check.…”
Section: Discussionmentioning
confidence: 99%
“…In order to detect errors made in the planning process, research has focused on designing manual and automated checks throughout this process 5–16 . Automated checks focus mainly on the technical integrity of a plan and on dosimetric metrics that are established for each treatment site.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, automated programs are mostly rule based and require continuous adaptation to ever changing clinical practices. Published studies, [3][4][5] including one from my institution, 5 showed that hybrid automated checks and manual checks catch…”
Section: A | Dr Ping Xiamentioning
confidence: 99%